PENGEMBANGAN SISTEM PENJADWALAN KULIAH MENGGUNAKAN ALGORITMA GENETIK (STUDI KASUS : PASCASARJANA UNIVERSITAS JAMBI) - Afrizal Nehemia Toscany; Rusdianto Roestam (LPPM Universitas Dinamika Bangsa, 2017)
Current scheduling classes at Jambi University graduate there are still some constraints such as thecreation of a relatively long schedules, conflicting schedules and schedule that does not correspond to thetime availability of the lecturers. Therefore, the author provides a solution in the form of lecturescheduling system using genetic algorithm with programming language PHP and the MySQL DBMS. Forsystem development method that is used is the waterfall. Lecture Schedule result generated by a systemthat has been built is becoming more precision with the allocated hours of teaching, classroom andprofessors. From the test results can also be concluded that the implementation of genetic algorithms is incompliance with the need to support the process of scheduling, so that scheduling can be done morequickly